Analysis of energy access and impact of modern energy sources in unelectrified villages in Uttar Pradesh - Sandwell,P; Chambon,C; Saraogi,A; Chabenat,A; Mazur,M; Ekins-Daukes,N; Nelson,J (Energy for Sustainable Development, 2016)
Bringingaccesstomodernenergysourcestothepoorestinsocietyisakeygoalofmanypolicymakers,businessesandcharities,butinorder tobea success projects and schemesmust be foundedonaccuratedata. We undertooka survey of energy demand and usage patterns in households in unelectrified villages in Uttar Pradesh, India toassess access to and utilisation of energy sources for lighting and cooking. The times of usage were recordedand analysed and the effect on usage patterns of transitioning from traditional to modern energy sourcesis assessed. We quantify the cost and greenhouse gas emissions of current energy use in order to provide abenchmark of potential mitigation through the use of renewable energy technologies: a typical householdwith kerosene lamps only for lighting spends INR 3243 (US$50.67) and emits 381 kgCO2eqper year; householdswithmoderncookingenergyspend17%morethroughincreasedusage,butemit28%lessgreenhousegasescom-pared to those with traditional stoves only. Cell phone ownership was found to be 50% amongst adults. We usedemographic and utilisation data to construct an hourly demand profile of basic electricity demand extrapolatedto each month of the year, and present an example of aspirational demand assess the impact of desirable appli-ances. A Monte Carlo simulation is used to highlight the daily and seasonal variation in total energy and powerdemand. A hybrid system, with solar power and battery storage meeting daytime demand and higher-capacitydiesel- or biomass-powered generation meeting the remainder during evening peaks and winter months,would satisfy demand most effectively.